Deslocados ambientais: migrações internacionais e reconhecimento da dignidade da pessoa humana pelo direito transnacional - Bicca, Júlia Fragomeni (2018)
What leads to carry out the present study is the fact that in some cases, some calamities the population can not return to the environment oforigin, often become uninhabitable, without drinking water, light, or simply because it has been devastated, as we can observe, at international level, the Maldives islands that are at risk of extinction due to the sea level rise due to the melting of the polar caps, thus the population that seek new place of residence, migrating to other States. The major problem lies in the fact that these individuals and groups that are driven by environmental degradation are not defined or protected in international laws and can be recognized as a new category, which has not yet been defined nomenclature, and can be called “environmental refugees”, “Environmental migrants. An analysis will be made of the current legislation to present important tools to assist the various international actors in the challenge of building a system of international legal protectionfor “environmental refugees” from a critical and multifaceted view of the problem with the help of transnational law, it will be sought to contribute to the important filling ofnormative lacuna of the International Law in the present time. For the present study, themonographic method will be used.